Coping strategies and emotional exhaustion in mothers of children with special needs during pandemic - Niamillah, Alfarida Afiqo; Hakim, Zun Azizul; Arnani, Ni Putu Rizky (Nusantara Journal of Behavioral and Social Science, 2024)
During the pandemic, many mothers of children with special needs have faced heightened emotional challenges, leading to increased emotional exhaustion. This study aims to examine the relationship between emotional exhaustion and coping strategies in these mothers, highlighting the importance of effective support mechanisms during this period. This quantitative research used non-probability sampling and included 80 mothers in Tulungagung. Data collection utilized two scales: one for emotional exhaustion and another for coping strategies, administered via questionnaires. Hypothesis testing indicated a significant relationship between emotional exhaustion and coping strategies, with F = 18.606 at p < 0.05. Emotional exhaustion accounted for 19% of the variance in coping strategies (R2=0.193), underscoring its impact. These findings suggest that addressing emotional exhaustion could improve coping strategies in mothers of children with special needs, potentially guiding more tailored support and interventions to alleviate stress and improve well-being.